Gesture recognition vehicle using PIC microcontroller - K. Selvakumar; Palanisamy R; M.Arun Noyal Doss; P. Gopi; A. Esakkipandi; L. Mathivadhanam; T. Abul Kalam Asath (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this paper we introduce a hand controlled robotic vehicle. Hand control robotic vehicle consists of a transmitter module and a receiver module. The transmitter will be placed on a hand glove and the receiver will be placed on the motor drive along with PIC microcontroller and motor driver IC. The RF transmitter sends commands to the IC which then forwards the commands to RF receiver. The RF receiver then sends the commands to PIC microcontroller on the vehicle which processes the commands so that the vehicle moves in the specified direction. It is having proposed utility in field ofconstruction, hazardous waste disposal and field  survey near borders etc. This project is developed as a travel buddy and industrial uses. Having future scope of advanced robotics that are designed and can be easily controlled using hand gesture only.